Occupational noise in the university setting: dosimetric assessment and strategies for exposure reduction - Torres-Cobo, Leyner; Alcázar-Espinoza, Javier; Vinueza-Morales, Mariuxi; Muñoz-Tarira, Andrea; Vidal-Silva, Cristian (Frontiers in Public Health, 2025)
PurposeThis study investigates occupational noise exposure in a university setting through dosimetric assessments conducted at Universidad Estatal de Milagro (UNEMI), Ecuador, by analyzing measurements collected in distinct campus areas during two periods, 2017 and 2025.MethodsSound pressure levels were measured across selected high-traffic and functional campus areas using standardized equipment in accordance with UNE-EN-ISO 9612:2009.ResultsMeasurements revealed an increasing trend in occupational noise exposure across university areas, with 2025 levels substantially exceeding recommended thresholds.ConclusionsThe findings emphasize the critical need for implementing targeted noise mitigation strategies to protect auditory health and preserve academic excellence within higher education institutions.ImplicationsAdopting these strategies can significantly reduce occupational health risks and foster a healthier, more effective academic environment. The study proposes comprehensive mitigation strategies tailored to university environments to address these challenges.